Emotion Regulation Under Pressure: The Effects of Mindfulness and Cognitive Reappraisal on Performance and Affect When Encountering Stress - Wolfe, Emma C. (Tufts Archival Research Center, 2020)
Individuals in high-stress occupations deal with a large volume of stressors that can increase anxiety and decrease job performance. Emotion regulation strategies such as mindfulness and cognitive reappraisal may counteract such negative outcomes. The purpose of this study was to examine the effects of brief training in mindfulness and cognitive reappraisal in the context of a virtual reality first-person shooter game. We hypothesized that brief training in mindfulness and/or cognitive reappraisal would decrease negative affective responses and increase task performance, and that these effects may be moderated a high or low level of induced psychological stress. Our sample size was 112 participants ages 18-35. Participants took part in two sessions across two days. In each session, they received mindfulness or cognitive reappraisal training or listened to a control script. They then used this training during an immersive virtual reality combat simulation, and we measured their self-reported anxiety and performance. Findings indicated that neither mindfulness nor cognitive reappraisal had a significant effect on performance, but cognitive reappraisal reduced self-reported anxiety. This indicates the potential of brief training as an effective method of reducing negative affect, perhaps building the foundation for the construction of a brief, evidenced-based cognitive reappraisal training program in the future.